Effect of high irradiation on photovoltaic power and energy - Nasrin, Rehena; Hasanuzzaman, Md.; Rahim, Nasrudin Abd (John Wiley & Sons, 2017)
Solar photovoltaics (PV) is a promising solution to combat against energy crisis and environmental pollution. However, the high manufacturing cost of solar cells along with the huge area required for well-sized PV power plants are the two major issues for the sustainable expansion of this technology. Concentrator technology is one of the solutions of the abovementioned problem. As concentrating the solar radiation over a single cell is now a proven technology, so attempt has been made in this article to extend this concept over PV module. High irradiation intensity from 1000 to 3000 W/m2 has been investigated to measure the power and energy of PV cell. The numerical simulation has been conducted using finite element technique. At 3000 W/m2 irradiation, the electrical power increases by about 190 W compared with 63 W at irradiation level of 1000 W/m2. At the same time, at 3000 W/m2 irradiation, the thermal energy increases by about 996 W compared with 362 W at 1000 W/m2 irradiation. Electrical power and thermal energy are enhanced by about 6.4 and 31.3 W, respectively, for each 100-W/m2 increase of solar radiation. The overall energy is increased by about 179.06% with increasing irradiation level from 1000 to 3000 W/m2. It is concluded that the effect of high solar radiation using concentrator can significantly improve the overall output of the PV module.